Strong correlation effects in vanadium oxide films - Skorenkyy, Yuriy; Kramar, Oleksandr; Dovhopyaty, Yuriy (Physics and Chemistry of Solid State, 2022)
In the present work the metal-insulator transition in doubly orbitally degenerated model of quasi-two- dimensional material based on V2O3 film, in which a crucial role is played by on-site Coulomb interaction and correlated hopping of electrons, has been investigated. With use of a projection procedure in the Green function method the energy spectrum of electrons has been calculated to model variations of the material properties at the temperature changes, the external pressure application and doping. The obtained expressions for thermodynamic potential and the energy gap widths allow analyzing the possible phase transitions in a system, the dependency of characteristics on the external actions for this strongly correlated material.